Answers

2014-07-09T16:29:24+05:30
As we know cos^2 +sin^2=1 now cubimg both side so {cos^2+ sin^2}^3= (1)^3
therefore by expanding we get cos^6 +sin^6+3cos^2 sin^4 +3sin^2 cos^4=1
therefore cos^6+sin^6 + 3cos^2sin^2 (cos^2+sin^2)=1
therefore cos^6+sin^6 +3cos^2 sin^2 =1
hence cos^6+sin^6= 1-3sin^2cos^2
1 5 1
pls mark as a best............. pls
Proof 1:sin^6 x + cos^6 x
= (sin^2 x + cos^2 x) ( sin^4 x - sin^2 cos^2 x + cos^4 x)
= (sin^4 x + cos^4 x) - sin^2 x cos^2 x
= (sin^2 x + cos^2 x)^2 - 2 sin^2 cos^2 x - sin^2 x cos^2 x
= 1 - 3 sin^2 x cos^2 x
Proof 2:
sin^6 x + cos^6 x
= (1 - cos^2 x)^3 + cos^6 x
= 1 - 3cos^2 x + 3cos^4 x - cos^6 x + cos^6 x
= 1 - 3cos^2 x(1-cos^2 x)
= 1 - 3 cos^2 x sin^2 x
Proof 1:
sin^6 x + cos^6 x
= (sin^2 x + cos^2 x) ( sin^4 x - sin^2 cos^2 x + cos^4 x)
= (sin^4 x + cos^4 x) - sin^2 x cos^2 x
= (sin^2 x + cos^2 x)^2 - 2 sin^2 cos^2 x - sin^2 x cos^2 x
= 1 - 3 sin^2 x cos^2 x
Proof 2:
sin^6 x + cos^6 x
= (1 - cos^2 x)^3 + cos^6 x
= 1 - 3cos^2 x + 3cos^4 x - cos^6 x + cos^6 x
= 1 - 3cos^2 x(1-cos^2 x)
= 1 - 3 cos^2 x sin^2 x
Proof 3:
sin^6 x + cos^6 x
= sin^6 x + cos^6 x + 3 sin^2 x cos^2 x - 3 sin^2 x cos^2 x
= sin^6 x + cos^6 s + 3 sin^2 x cos^2 x (sin^2 x + cos^2 x) - 3 sin^2 x cos^2 x
= 1 - 3sin^2 x cos^2 x
Proof 4:
sin^6 x + cos^6 x
= sin^6 x + cos^6 x - 1 + 1
= sin^6 x + cos^6 x - (sin^2 x + cos^2 x)^3 + 1
= sin^6 x + cos^6 x - sin^6 x - 3sin^4 x cos^2 x - 3 sin^2 x cos^4 x - sin^6 x + 1
= 1 - 3 sin^2 x cos^
The Brainliest Answer!
2014-07-09T16:46:08+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
 Sin ^{6} A + Cos^{6} A 
[Sin ^{2} A]^3 + [Cos ^{2}]^3                [.·. (a³+b³)= (a+b) (a²-ab+b²) ]

(Cos^{2} A + Sin^{2} A) (Cos^{4} A-Cos^{2} A. Sin^{2} A+ Sin^{4} A)
(Sin^{4} A + Cos^{4} A) - Sin^{2} A.Cos^{2} A
(Sin^{2}A+Cos^{2}A)^{2} -2Sin^{2}A.Cos ^{2}A-Sin^{2}A.Cos^{2}A

[.·. Cos²A+Sin²A=1]

⇒1-3Sin^{2}A.Cos^{2}A               
[Hence, proved]






2 5 2
Proof 1:sin^6 x + cos^6 x
= (sin^2 x + cos^2 x) ( sin^4 x - sin^2 cos^2 x + cos^4 x)
= (sin^4 x + cos^4 x) - sin^2 x cos^2 x
= (sin^2 x + cos^2 x)^2 - 2 sin^2 cos^2 x - sin^2 x cos^2 x
= 1 - 3 sin^2 x cos^2 x
Proof 2:
sin^6 x + cos^6 x
= (1 - cos^2 x)^3 + cos^6 x
= 1 - 3cos^2 x + 3cos^4 x - cos^6 x + cos^6 x
= 1 - 3cos^2 x(1-cos^2 x)
= 1 - 3 cos^2 x sin^2 x
Proof 3:
sin^6 x + cos^6 x
= sin^6 x + cos^6 x + 3 sin^2 x cos^2 x - 3 sin^2 x cos^2 x
= sin^6 x + cos^6 s + 3 sin^2 x cos^2 x (sin^2 x + cos^2 x) - 3 sin^2 x cos^2 x
= 1 - 3sin^2 x cos^2 x
Proof 4:
sin^6 x + cos^6 x
= sin^6 x + cos^6 x - 1 + 1
= sin^6 x + cos^6 x - (sin^2 x + cos^2 x)^3 + 1
= sin^6 x + cos^6 x - sin^6 x - 3sin^4 x cos^2 x - 3 sin^2 x cos^4 x - sin^6 x + 1
= 1 - 3 sin^2 x cos^